The basics of community health nursing : a study guide for nursing students and local board examinees - Gesmundo, Monina H. (Quezon City, Philippines : C & E Publishing Inc., 2010)
This book presents CHN concepts in a simple yet comprehensive manner.
Unit 1: Safe and quality care, health communication, collaboration and teamwork in CHN -- Unit 2: Selected Public Health Programs -- Unit 3: Research and quality improvement -- Unit 4: Management of resources and environment and records management
Keywords: COMMUNITY HEALTH NURSING